Disturbance of gene expression in primary human hepatocytes by hepatotoxic pyrrolizidine alkaloids: A whole genome transcriptome analysis. Issue 7 (October 2015) - Luckert, Claudia; Hessel, Stefanie; Lenze, Dido; Lampen, Alfonso
Highlights Structurally different PA highly disturb gene expression in primary human hepatocytes. PA deregulate numerous phase I and II enzymes as well as transport proteins. PA affect cell cycle regulation, cell death and development of cancer. PA interfere with lipid metabolism and bile acid flow.